The Role of debris flows in the origin and evolution of gully systems on crater walls: martian analogs in meteor crater, arizona (usa) - Palucis, Marisa C.; Dietrich, William E.; Howard, Alan (Italian journal of engineering geology and environment, 2011)
In 1999, the Mars Global Surveyor acquired images of young gully features on the walls of impact craters. From these and subsequent images, numerous theoretical and physical models have been developed based primarily on three competing theories about the origin of the gullies: 1) scour and deposition by dry granular flows, 2) debris flow driven gully incision due to the sudden release of gases or fluid from the subsurface, or 3) fluid incision via debris flows due to the release of surface volatiles or the melting of ice. To contribute insights and possible constraints on these competing mechanisms, we are performing an intensive investigation of the origin and evolution of the gullies in Meteor Crater, a well-preserved terrestrial analogue. The location of the gullies along radial fractures in the crater wall and the presence of lake sediments on the crater floor have lead researchers to conclude that groundwater seepage and fluvial incision formed the gullies. However, from initial field observations and inspection of high-resolution LiDAR data, we have observed that the gullies: 1) show evidence of multiple events, 2) do not cross the crater floor, 3) have modest size levees, and 4) terminate on an ~8- 15o slope. As an alternative to current interpretations, we suggest that gully incision was caused by debris flows driven by periodic snowmelt during the cooler and wetter Pleistocene.